(A study on isothermic-sorption models for desiccated coconut made of hybrid coconuts (khina-1,khina-2 dan Khina-3) - Damerys Sirait, Shinta; Marlina R. Sirait, Marlina R. Sirait; Mahdar, Putiati (Balai Besar Industri Agro, 1995)
A study on isothermic-sortion characteristics of some desccated coconut had been conducted.The desiccated coconut was made from hybrid coconuts,khina-1,khina-2 ,khina-3.The result showed that the moisture content equilibrium range of dessicated coconut made from khina-1,khina -2,and khina-3was respectively 2.42-10.43%(db),2.27-13.66%(db)and 2.47-11.49%(db)due to adsorbtion approach,whereas by desortion it was 22.66-46.94%(db),3749-57.56%(db)43.95-62.97%(db).The reseach proved thet Henderson Equation was the most suitable to describe the isothermic-sorption models of desiccated coconut made from those hybrid coconuts.By knowing the moisture content equilibrium and isothermic-sorptionmodels of those desiccated coconuts,the storage condition to maintain the quality required can be designed.